2015
DOI: 10.3349/ymj.2015.56.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values of Body Composition Indices: The Korean National Health and Nutrition Examination Surveys

Abstract: PurposeAn increase in the prevalence of obesity has been observed in children and adolescents. As remarkable changes in body composition occur with growth during the adolescent period, it is important that changes in body composition be monitored. The purpose of this study was to propose reference percentile values for body composition indices including body mass index (BMI) in children and adolescents in Korea.Materials and MethodsThis study was performed using data from the Fourth and Fifth Korea National He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…For those who had DXA as a reference: Park et al 11 evaluated 689 asian teenagers aged between 12 and 16 years who reported a decrease of the %BF in this age range, as shown in our results. In the 50 th percentile the values varied from 25.2% to 19.4%; in the 90 th percentile the values varied between 37.1% and 29.5%.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…For those who had DXA as a reference: Park et al 11 evaluated 689 asian teenagers aged between 12 and 16 years who reported a decrease of the %BF in this age range, as shown in our results. In the 50 th percentile the values varied from 25.2% to 19.4%; in the 90 th percentile the values varied between 37.1% and 29.5%.…”
Section: Discussionsupporting
confidence: 72%
“…Around the world, studies of reference values based on fat percentage of children and adolescents obtained through ST were related in Germany (3-18 years) 5 ; Canada (6-19 years) 7; United States (5-18 years) 8 ; Turkey (6-18 years) 9; Brazil (7-10 years old) 19 and India (10-19 years) 11 . On the other hand, studies that used DXA were found of the population of Denmark (8-14 years) 2) ; United States (8-19 years) 25 and Korea (10-18 years) 10 (10-19 years) 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Signs of portal hypertension, such as splenomegaly, ascites or varices, were collected based on the US, clinical or endoscopic results. Body mass index (BMI) at the time of 2D SWE was defined as normal for percentiles lower than 85, overweight for percentiles between 85 and 95, and obese for percentiles of 95 or higher [22,23].…”
Section: Examinations In Children With Biliary Atresiamentioning
confidence: 99%